2021
DOI: 10.2147/jpr.s332509
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Analysis of the High-Intensity Zone on Lumbar Spine Magnetic Resonance Images: Classification, Features and Correlation with Low Back Pain

Abstract: Aim Early studies suggested that the high-intensity zone (HIZ) on lumbar MRI was a diagnostic sign of painful internal disc disruption (IDD). However, recent studies have questioned its diagnostic value. This study is conducted to explore imaging features of HIZ and to investigate the correlation between these characteristics and low back pain (LBP), further studying the predictive value of HIZ. Methods A retrospective study of 1188 cases was performed. MR images were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The High-Intensity Zone (HIZ) findings explain that changes in certain metabolites in the intervertebral disc are the direct cause of discogenic pain. 19 Nonetheless, this finding has not been effectively validated in metabolite validation and molecular level studies. This study established a rat discogenic pain model by injection of PBS to disc-puncture IDD model to induce pain.…”
Section: Discussionmentioning
confidence: 99%
“…The High-Intensity Zone (HIZ) findings explain that changes in certain metabolites in the intervertebral disc are the direct cause of discogenic pain. 19 Nonetheless, this finding has not been effectively validated in metabolite validation and molecular level studies. This study established a rat discogenic pain model by injection of PBS to disc-puncture IDD model to induce pain.…”
Section: Discussionmentioning
confidence: 99%
“…The visibility of HIZ on several slices seems a reliable indicator for CLBP compared with patients with HIZ visible on only one slice. 24 Slight edema of the anterior vertebral margin is sometimes visible (or sclerosis on radiographs/CT) and must not Fig. 2 Lateral radiograph centered at L3-L4 and L4-L5 levels in an 80year-old patient.…”
Section: Disk Fissuresmentioning
confidence: 99%
“…The visibility of HIZ on several slices seems a reliable indicator for CLBP compared with patients with HIZ visible on only one slice. 24…”
Section: Pure Painful Syndromesmentioning
confidence: 99%
“…Recent epidemiological and clinical studies have reported that intervertebral disc (IVD) degeneration is associated with the occurrence of LBP [ 2 , 3 , 4 , 5 ]. Clinically, IVD degeneration is well assessed using magnetic resonance imaging (MRI), and its severity and characteristic findings are reported to be associated with discogenic LBP [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%